Ammonia Emission and Deposition in Scotland and Its Potential Environmental Impacts. (2004) - Sutton, M.A.; Dragosits, U.; Hellsten, S.; Place, C.J.; Dore, A.J.; Tang, Y.S.; van Dijk, N.; Love, L.; Fournier, N.; Vieno, M.; Weston, K.J.; Smith, R.I.; et al.
Abstract : The main source of atmospheric ammonia (NH3 ) in Scotland is livestock agriculture, which accounts for 85% of emissions. The local magnitude of emissions therefore depends on livestock density, type, and management, with major differences occurring in various parts of Scotland. Local differences in agricultural activities therefore result in a wide range of NH3 emissions, ranging from less than 0.2 kg N ha −1 year −1 in remote areas of the Scottish Highlands to over 100 kg N ha −1 year −1 in areas with intensive poultry farming. Scotland can be divided loosely into upland and lowland areas, with NH3 emission being less than and more than 5 kg N ha −1 year −1, respectively.Many semi-natural ecosystems in Scotland are vulnerable to nitrogen deposition, including bogs, moorlands, and the woodland ground flora. Because NH3 emissions occur in the rural environment, the local deposition to sensitive ecosystems may be large, making it essential to assess the spatial distribution of NH3 emissions and deposition. A spatial model is applied here to map NH3 emissions and these estimates are applied in atmospheric dispersion and deposition models to estimate atmospheric concentrations of NH3 and NH4 +, dry deposition of NH3, and wet deposition of NHx. Although there is a high level of local variability, modelled NH3 concentrations show good agreement with the National Ammonia Monitoring Network, while wet deposition is largest at high altitude sites in the south and west of Scotland. Comparison of the modelled NHx deposition fields with estimated thresholds for environmental effects ("critical loads") shows that thresholds are exceeded across most of lowland Scotland and the Southern Uplands. Only in the cleanest parts of the north and west is nitrogen deposition not a cause for concern. Given that the most intense effects occur within a few kilometres of sources, it is suggested that local spatial abatement policies would be a useful complement to traditional policies that mitigate environmental effects based on emission reduction technologies.